GENDER DIFFERENCES IN ENGLISH LANGUAGE LEARNING - Tarina Dashela; Yeni Mustika (STBA Pontianak, 2022)
This article focused on the gender differences in English Language Learning. It discovers students’ learning styles as affected by the notions about men’s and women’s differences in communication. The data were randomly collected from ten male and ten female students of the English department of Tanjungpura University Pontianak. The population was the third-semester students of English department students. They were given an online questionnaire through Google Form. It is to find out their attitudes towards speaking to a different gender, strategy to express an opinion, group work preferences, and activeness/passiveness in the class. The findings showed some factors affect the different styles of female and male students in learning English. The result of the data indicated that more females felt reluctant to speak English to a different gender. Besides, it can also affect the successful strategies of English students in learning English. The great potency of female students to be ashamed, nervous, and women’s language can affect their achievement in English. Meanwhile, male students as influenced by their need to challenge and maintain strength as men and can use speaking English ability as a way to show their status as men.